2018
DOI: 10.1590/1413-81232018236.07932018
|View full text |Cite
|
Sign up to set email alerts
|

Federalismo e políticas de saúde no Brasil: características institucionais e desigualdades regionais

Abstract: This article analyses the main characteristics of federalism in Brazil and its institutional relations with health policy. It discusses federalism from a classical perspective highlighting the essentially centralized nature of Brazil's system and the prevalence of decentralizing health policies underpinned by the principles enshrined by the 1988 Constitution.We used primary data obtained from an electronic questionnaire responded by secretaries of health sitting on the governing bodies of the country's health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 19 publications
1
12
0
13
Order By: Relevance
“…David et al [ 50 ] and Santos et al [ 51 ] also reported better performance at primary healthcare in the poorest municipalities. Worse performance at primary healthcare in the richest municipalities may be associated with higher private health insurance coverage, supply of inpatient and outpatient facilities (secondary, tertiary and quaternary care), and lower primary healthcare coverage [ 52 – 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…David et al [ 50 ] and Santos et al [ 51 ] also reported better performance at primary healthcare in the poorest municipalities. Worse performance at primary healthcare in the richest municipalities may be associated with higher private health insurance coverage, supply of inpatient and outpatient facilities (secondary, tertiary and quaternary care), and lower primary healthcare coverage [ 52 – 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is evident that nursing, among the various health professions, has assumed positions of direction and management, which requires from the nurse leadership skills such as flexibility, ability to discern the needs of the people supervised, and mainly the motivation of employees, making the most of their skills without exploiting them [17][18][19] .…”
Section: Management Practices and The Incorporation Of Nursing Profesmentioning
confidence: 99%
“…On the other hand, the persistence of a shortage of health professionals 11 , and regional disparities in the quality of care persisted, mainly revealing the influence of socioeconomic factors 12 , as shown by the comparison of the average income of the wealthiest segment of the population with that of the poorest segment: the wealthiest 20% have an income 17 times higher than the income of the poorest 20% 13 .…”
Section: The Trend Of People's Health Conditions and Health Servicesmentioning
confidence: 99%